POP UP BOOK DESIGN AS AN INTRODUCTION MEDIA ABOUT PROFESSION FOR EARLY CHILDREN - Widhiastuti, Reni (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The purpose of this project is to produce a pop-up illustration book design that serve as educational media for the introduction of a variety of professions for children. The media used are digital print on hardcover paper for cover and Ivory 230 gsm paper for book contents. The technique of work is done starting from making storyboards on HVS paper, then making sketches and coloring digitally to then be printed and formed pop up pages manually. Each completed pop up page is then put together to be bound into a book. The work process includes: (1) Idea Search, (2) Goal Setting, (3) Analysis of Target Audience, (4) Pre Production, covering content design, character drawing, storyboard design, (5) Production, including sketches and pop up designs , coloring, giving text, pasting and finishing, (6) Post Production. In making the entire work pay attention to the elements and design principles. The work produced is a pop up illustration book of types of professions with a size of 20cm x 18cm. Characteristics of illustrated works created using a cartoonal approach.